2005
DOI: 10.1515/jpm.2005.023
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of amino-terminal probrain natriuretic peptide levels in preeclampsia and normotensive pregnancy

Abstract: The higher levels of serum Nt pro-BNP in preeclamptic women may be an indicator of high left-ventricular filling pressure, and indicate left-ventricular diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 12 publications
2
31
3
1
Order By: Relevance
“…In this manner, we compared the impact of preeclampsia prediction of NT-proBNP with notch positivity together with elevated PI values. Unlike in other studies, NTproBNP levels were not different with respect to the development of preeclampsia in later pregnancy [8,13,22]. The lack of difference may be related to some reasons.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…In this manner, we compared the impact of preeclampsia prediction of NT-proBNP with notch positivity together with elevated PI values. Unlike in other studies, NTproBNP levels were not different with respect to the development of preeclampsia in later pregnancy [8,13,22]. The lack of difference may be related to some reasons.…”
Section: Discussioncontrasting
confidence: 88%
“…In the present study, NT-proBNP levels were measured during the 21st-24th week. However, Fleming et al and Kale et al [8,13] reported their results after 34-35 weeks. This period is when placentation is completed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kale, et al reported that NT-proBNP was significantly higher in pregnant women with pregnancy-induced hypertension with left ventricular diastolic dysfunction than in normotensive pregnant women. 27) Rafik, et al evaluated echocardiograms and NT-proBNP levels and reported that left ventricular diastolic function in pregnant women with pregnancy-induced hypertension was significantly lower than in normal pregnant women. 28) An increase in troponin T concentration in the blood is a biomarker of damaged cardiac muscle cell membrane.…”
Section: Discussionmentioning
confidence: 99%